2017
DOI: 10.1016/j.foodchem.2017.02.056
|View full text |Cite
|
Sign up to set email alerts
|

Effects of konjac glucomannan on heat-induced changes of wheat gluten structure

Abstract: Effects of konjac glucomannan on the structure of wheat gluten were investigated at variable temperatures in this study. Dynamic oscillatory rheology study showed that konjac glucomannan conferred stiffness on gluten with a higher tan δ data at 25°C and 55°C, but this parameter was lower at 75°C and 95°C. Konjac glucomannan decreased the content of thiol equivalent groups and increased the α-helix/β-sheet content ratio, respectively. The thicker layer of gluten protein with 5% konjac glucomannan was observed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(48 citation statements)
references
References 36 publications
2
44
2
Order By: Relevance
“…The WG had better hydration capacity to form a dough with higher viscosity, which could prevent the flowing of melt during extrusion leading to a lower mass flow rate (Wang et al, 2017). So that the SME was increased significantly when blending PPP with WG (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The WG had better hydration capacity to form a dough with higher viscosity, which could prevent the flowing of melt during extrusion leading to a lower mass flow rate (Wang et al, 2017). So that the SME was increased significantly when blending PPP with WG (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, it increased from 836.40 to 881.82 kJ kg À1 (P < 0.05) when the ratio of WG increased from 20% to 60%, which might be due to the viscosity increased and screw wear brought by the WG (Zarzycki et al, 2015). The increase in the viscosity also indicated that higher degree of aggregation might occur in the PPP-WG mixtures, which could entrap more water due to the greater effective volume of the aggregates (Zhang et al, 2016a;Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…When compared with intact MP and HMP, the most obvious change in C2 was the decrease of b-sheets and the increase of b-turns (1678 and 1692 cm À1 ). Wang et al (2017b) also reported that the heat treatment of wheat gluten caused a decrease in bsheets. When compared the spectra of GHMP and GMP with that of C2, there were two bands at 1678 and 1692 cm À1 were shifted to 1682 and 1694 cm À1 , respectively, and a new band at 1650 cm À1 appeared.…”
Section: Ftir Analysismentioning
confidence: 93%
“…Compared to the control, the content of b-turn was slightly increased with BWG supplementation. These b-turns can be formed from b-sheets (Wang et al, 2017). The b-turn structure is considered as an open reverse turn, resulting in fewer hydrogen bonds was required to bond b-sheet structure than the multi-hydrogen (Tatham et al, 1985).…”
Section: Ft-ir Spectroscopy Analysis Of the Doughmentioning
confidence: 99%